Analisis Kewirausahaan dalam Pengembangan Rencana Bisnis UMKM Kuliner: Studi Kasus Pada UMKM Kuliner di Kota Sidoarjo - Putra, Andri Nusantara; Mubarok, M. Dzulfahmi; Karyanto, Frendika Eko; Ridlo, Muhammad; Setyagraha, Javan Agustian; Setiyawan, Iskandar; Rahmawati, Imelda Dian (Universitas Hamzanwadi, 2025)
The purpose of this study is to evaluate the role of entrepreneurship in creating business plans for culinary UMKM in Sidoarjo City and to identify the key success factors for culinary business owners. This study employs a qualitative descriptive approach, which involves 50 culinary UMKM operating for more than two years. Data were collected through in-depth interviews and direct observations, focusing on product innovation, digital marketing, financial strategy, location selection, and risk management. The research results indicate that the most influential factors in the success of culinary businesses in Sidoarjo are digital marketing and product innovation. Through thematic analysis and data triangulation, it was found that UMKM entrepreneurs are generally proactive and innovative in adapting to market trends and leveraging digital marketing to reach consumers. Other factors, such as financial strategy and location selection, also support business sustainability. This study is expected to provide practical guidance for aspiring entrepreneurs in developing successful and sustainable culinary business plans